SIKAP RELIGIUS REMAJA TERHADAP KOMUNITAS BALAP LIAR - Muhammad salman al farizy; Dzulfikar Akbar Romadlon (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The phenomenon of illegal racing in Indonesia is a social problem that often involves teenagers and receives media attention. Illegal racing is a motorized racing activity carried out on the highway without official permission, often causing noise and endangering safety. This study aims to understand adolescents' religious attitudes towards the phenomenon of illegal racing by exploring their understanding of religious values as well as factors that influence these attitudes, such as religious education, social environment, and peer influence. The research method used is a phenomenological case study, with data collection through in-depth interviews, participatory observation, and analysis of related documents. The results show that teenagers with a strong religious understanding tend to reject illegal racing because it contradicts religious values. In contrast, adolescents who lack strong religious education or are influenced by negative social environments are more likely to engage in this practice. This study provides insights into the importance of religious education and social norm enforcement in reducing the phenomenon of illegal racing, and offers a basis for the development of more effective religious education programs and policies that can improve community safety and well-being